Improving spinal alignment through innovative resistance training with outdoor fitness equipment in middle-aged and older adults: a randomized controlled trial - P. J. Marcos-Pardo; T. Abelleira-Lamela; R. Vaquero-Cristóbal; A. Espeso-García; F. Esparza-Ros; N. González-Gálvez (Scientific Reports)
Abstract The main objective of this study was to analyze the effect of a resistance training program using outdoor fitness equipment (OFE) on sagittal spine disposition and pelvic tilt in middle-aged and older adults. One hundred and twenty-eight middle-aged and older adults were randomly assigned to the training (TG) or control group (CG). The TG trained for 8 weeks, with 2 weekly sessions of one hour of resistance circuit training with OFE. Before and after the intervention, the sagittal spine disposition and pelvic tilt in the relaxed standing and sitting positions were analyzed. The results showed that the TG obtained a significant reduction (p < 0.001) in all the curvatures of the sagittal spine disposition and pelvic tilt in the standing position after the intervention, in contrast to the CG, which only showed a significant reduction in pelvic tilt (p = 0.005). Regarding the sitting position, only the TG presented a significant decrease in lumbar lordosis (p < 0.001). In conclusion, resistance training with OFE may be useful in improving sagittal spine disposition in middle-aged and older adults. Given the availability of free OFE in parks, the present research provides elders with an accessible and effective training program to curb the effects of ageing on the sagittal spine disposition.